As políticas de imigração no Brasil nos séculos XIX e XX e o desenvolvimento de territórios: estudo de caso da Colônia Dom Pedro II - Campo Largo - Paraná - Sikora, Mafalda Ales (2014)
This research aims to analyze the influences of Brazilian immigration policies of the nineteenth and twentieth centuries in the development of the colony Dom Pedro II (Campo Largo - Paraná) from the perspective of the descendants of Polish immigrants. Through the case study, a method of scientific work, and through the techniques of documentation, bibliographic and field research, was developed an investigation on the territory of Cologne. As main results, it was found that the immigration policies of the nineteenth and twentieth century has favored the formation of colonies of immigrants from different regions of Brazil. In Paraná State, one of them was the Cologne Dom Pedro II (1876), formed by Polish immigrants. Since its implementation, this Colony passed socioeconomic, political and cultural changes, impacted by immigration policies from the periods imperial, the transition from the end of slavery and the republic. The Colony it was structured and developed from the immigration policies of the government, with the important support of the Catholic Church. In economics, the changes occurred mainly in agricultural production systems. From the familiar subsistence farming, for traditional farming, mechanized agriculture, agribusiness and rural tourism.